2014
DOI: 10.1103/physrevb.90.094101
|View full text |Cite
|
Sign up to set email alerts
|

Role of magnetic degrees of freedom in a scenario of phase transformations in steel

Abstract: Diversity of mesostructures formed in steel at cooling from high temperature austenite (γ) phase is determined by interplay of shear reconstructions of crystal lattice and diffusion of carbon. Combining first-principle calculations with large-scale phase-field simulations we demonstrate a decisive role of magnetic degrees of freedom in the formation of energy relief along the Bain path of γ-α transformation and, thus, in this interplay. We show that there is the main factor, namely, magnetic state of iron and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 37 publications
4
42
0
7
Order By: Relevance
“…This is also supported by a recent work from Razumov et al [50], which reported that the short-range FM ordering in PM austenite is essential for the martensitic transformation of the Fe lattice. Second, as reported by Okatov et al [46], the exchange parameter J of fcc Fe shows a clear FM ordering with increasing volume and tetragonality.…”
Section: Magnetic State At the Austenite/ferrite Interfacesupporting
confidence: 70%
“…This is also supported by a recent work from Razumov et al [50], which reported that the short-range FM ordering in PM austenite is essential for the martensitic transformation of the Fe lattice. Second, as reported by Okatov et al [46], the exchange parameter J of fcc Fe shows a clear FM ordering with increasing volume and tetragonality.…”
Section: Magnetic State At the Austenite/ferrite Interfacesupporting
confidence: 70%
“…The energies of various phases were compared and the respective correct values of magnetic moments at zero temperature were obtained within these studies 1,3,4 . The combination of these methods with the Heisenberg model gave a possibility to treat magnetic correlations (also at finite temperature), and provided an accurate value for the Curie temperature of bcc Fe 5,6 , its thermodynamic properties 7,8 , and magnon-phonon coupling 9 . This combination also resulted in an accurate value for the alpha-gamma transition temperature as a function of carbon concentration 8 .…”
mentioning
confidence: 99%
“…где F el.in -энергия деформационного взаимодействия углерода с напряжениями, создаваемыми растущей коло [18,20,27]. Энергии α и γ фаз в присутствии уг-лерода (или без него) были рассчитаны ab initio для парамагнитного и ферромагнитного состояний.…”
Section: формулировка моделиunclassified
“…При σ n = 0 распад развивается по классическому сценарию роста выделения феррита [27], и соответству-ющие расчеты здесь не приводим.…”
Section: результаты моделирования и обсуждениеunclassified
See 1 more Smart Citation